Case report: Spindle cell sarcoma and pituitary adenoma in the sella region—a rare collision tumor - Ding, Peng-fei; Zhu, Ting; Cui, Yue; Yan, Hui-ying; Wang, Yun-feng; Hang, Chun-hua; Li, Wei (Frontiers in Oncology, 2024)
BackgroundCollision tumors are defined as two or more distinctly bordered, mutually invasive tumors in the same anatomical region. Characterized by low incidence and lack of specificity, they often pose a significant challenge to disease diagnosis. Among these, collision tumors in the sella region are incredibly rare.Case descriptionOn 13 June 2023, the Department of Neurosurgery at Drum Tower Hospital admitted a patient with a pituitary adenoma in the sella region complicated by spindle cell sarcoma. After reviewing the literature, no related cases were reported. A patient presenting with complex clinical symptoms and preoperative imaging showing occupancy in the sella region is considered to have a recurrence of pituitary adenoma. After thorough preoperative evaluation and discussion, a trans-sphenoidal approach (with the aid of an endoscope) was performed to resect the pituitary lesions. Combined with postoperative pathological tissue and imaging, the patient was diagnosed with a pituitary adenoma (postoperative recurrence) in the sella region complicated by spindle cell sarcoma. The patient made a fair recovery and was discharged on the 8th postoperative day.ConclusionThis case report aims to elucidate and discuss the diagnosis and screening of rare collision tumors in the sella region to reduce the misdiagnosis rate and provide accurate treatment.